Lorlatinib in the treatment of a rare pulmonary mucoepidermoid carcinoma with EML4-ALK fusion: a case report and literature review - Xu, Zijun; Cong, Xiaofeng; Liu, Ziling (Frontiers in Oncology, 2024)
Pulmonary mucoepidermoid carcinoma (PMEC) is a rare tumor with limited clinical data available due to its low incidence. So far, there are no universal treatment guidelines for this malignant tumor. We present here the case of a 59-year-old female never smoker who was initially referred to our hospital with cough and hemoptysis and was eventually diagnosed with PMEC. Based on further genetic testing, echinoderm microtubule-associated protein-like4-anaplastic lymphoma kinase (EML4-ALK) fusion variants E20:A20 (V2) was found. The patient was treated with lorlatinib as the first-line treatment. This case is the first to describe the effectiveness of lorlatinib in treating an advanced high-grade PMEC with EML4-ALK fusion V2 mutation patient.